Innovations in government research, recognition, and replication - Borins, Sandford F. 1949- (Innovative governance in the 21st century, 2008)
"Answers questions on the future of government innovation and its effect on citizens and democratic governance by presenting a comprehensive approach to advancing the practice and study of innovation in government. Discusses new research on innovation, explores the impact of programs that recognize innovation, and considers challenges to replicating innovations"--Provided by publisher.